THE ROLE OF PLAYING IN ENHANCING SOCIAL-EMOTIONAL COMPETENCE IN EARLY CHILDHOOD EDUCATION - Puspita, Kiki; Fauziyah , Rofiatul; Imamah, Imamah (Program Studi Pendidikan Guru Sekolah Dasar Fakultas Pendidikan Ilmu Pengetahuan Sosial dan Bahasa Institut Pendidikan Tapanuli Selatan, 2025)
Abstract This study explores the role of play in enhancing the social and emotional development of early childhood learners within the Indonesian preschool (PAUD) context. Drawing from a literature review and observational research in a Central Jakarta kindergarten, the study highlights the significance of various types of play—particularly symbolic play, role-play, and cooperative play—in developing key competencies such as empathy, self-regulation, social communication, and emotional awareness. The findings demonstrate that structured play activities, when facilitated by educators, can help children who are initially shy or withdrawn to become more confident, emotionally expressive, and socially engaged. The study underscores the importance of integrating play-based learning into early childhood education curricula and provides practical recommendations for educators and policymakers. It concludes that play is not merely recreational but a foundational strategy for shaping children’s character and emotional well-being from an early age. Keywords: play-based learning; early childhood education; social-emotional development; role-play; cooperative play; preschool education; emotional intelligence.